Hygiene sanitary conditions in production of artisanal cheese made in Uberaba – MG - Clenilson Gonçalves dos Santos; Emiliane Andrade Araújo Naves; Aline Dias Paiva; Priscila C. B Vianna; Fernanda T. Toloi (Revista do Instituto de Latícinios Cândido Tostes, 2018)
The Artisanal cheese is one of the oldest cheeses produced in Brazil, and plays an important economic and sociocultural role in the producing regions. The cheese is made from raw milk, which generates greater concern regarding the good manufacturing practices, since there is a risk of consumer exposure to pathogens and/or their toxins. In this context, this study aimed to perform the sanitary diagnosis of artisanal cheese produced in the city of Uberaba-MG. Fifteen producers were selected, and a questionnaire was applied to evaluate the hygienic-sanitary conditions of the facilities and the cheese processing, as well as the knowledge of the producers on the legislation and good manufacturing practices. Microbiological analyzes of water, milk and cheese were performed on six of the selected properties. The results indicate that 87% of the interviewed producers did not use the “pingo” in cheese production and, on average, they marketed the cheese three days after production, which characterizes non-compliance with current legislation. In addition, none of the properties performs the water chlorination, a behavior that can compromise the microbiological quality of the product. According to the results obtained, 46% of the producers are not aware of the priorities for requesting the regularization of dairy products at the Institute of Agriculture of Minas Gerais. Regarding the microbiological analysis of artisanal cheese, all the evaluated parameters were above the limits established by current legislation. Therefore, it is concluded that the producers are not aware of the legislation and there is a clear need for training of these producers in good manufacturing practices.